(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article is devoted to the peculiarities of marketing tools in retail. The need to use marketing tools for retail in the modern market is a requirement of the time. The use of several marketing tools allows you to comprehensively solve the problems of firms.